Eksistensi Jaminan Fidusia Sebagai Langkah Perlindungan Hukum Bagi Kreditur Dalam Akad Murabahah: Studi Kasus Putusan Mahkamah Agung No. 452k/Ag/2016 - Muktar Bebi Saputra (Universitas Islam Indonesia, 2020)
The development of financial institutions in Indonesia can be seen from the increasing number of non-bank financial institutions that have sprung up so that they may become an alternative to financial institutions other than banks to meet the needs of the community. One of them is financing institutions, especially those that use fiduciary guarantees which are considered to have a separate existence in terms of legal protection for creditors. Fiduciary guarantees are often applied in Murabahah financing contracts. Therefore, this study examines two problems, namely: First, how is the existence of fiduciary security as a measure of legal protection for creditors? Second, what is the legality of the fiduciary guarantee in the murabahah contract? This research is normative in nature, where the results conclude that: fiduciary guarantee which is an additional guarantee (accessoir) while the Murabahah contract is the primary agreement, therefore the existence of the fiduciary guarantee depends on the Murabahah contract itself; while the form of legality of the fiduciary guarantee in the murabahah contract is in the application of the precautionary principle.